The analysis of the access to information regarding the adoption of innovation, in Buzau County, Year 2012 - Raluca Necula (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
The information represents the engine of development both for the individual and for society. I watched by our analysis to make a link between the possibility of accessing information and the respondents, in order to understand the consequences of adoption of innovation, and disseminating them. The study was done in Buzau County, in the communes of Bisoca, Pietroasele and Gheraseni, a total of 90 people. The importance of understanding the concept of innovation, the implementation of new in households, it is great, just by getting more information and free access to reach an optimum development of the agriculture.In our study we wanted to touch several points of interest with regard to access to information with a view to their adoption of the innovation in agriculture, i looked through most of the information ways , evaluating the autodidactic profile and access to technical updates.
Keywords: 330; innovation; technical news; information; questionnaire